Stable isotope records of sei whale baleens from Chilean Patagonia as archives for feeding and migration behavior - Reiss, Lilian; Häussermann, Verena; Mayr, Christoph (Ecology and Evolution, 2019)
Carbon (δ13C) and nitrogen (δ15N) stable isotope variations in baleen plates of sei whales (Balaenoptera borealis) stranded after a mass mortality event in Chilean Patagonia were investigated to assess potential dietary and migratory patterns. Carbon and nitrogen isotope ratios of seven baleens from six individuals were analyzed. The δ13C values ranged from − 19.1 to − 15.9‰ and the δ15N values from 8.7 to 15.4‰. Variations of up to 2.9‰ for δ13C and 5.3‰ for δ15N were observed within one baleen. Carbon and nitrogen isotope records of each baleen were significantly correlated and showed recurring oscillations confirmed by wavelet analyses. Oscillations slightly differed in periodicity indicating variable baleen growth rates between 10.0 and 16.5 cm/year. Food sources of the whales are discussed in terms of available isotope data for potential prey taxa and potential migratory behavior on the basis of latitudinal isotope gradients of particulate organic matter. Cyclicity could be explained by regular migrations of the sei whales from subtropical calving areas to high-latitude foraging grounds. δ15N records of baleens differed between individuals eventually pointing to diverse feeding and migratory preferences among sei whale individuals.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Balaenoptera borealis; baleen growth rate; carbon isotopes; mass mortality event; nitrogen isotopes; Patagonian fjords